2005
DOI: 10.3733/ca.v059n04p229
|View full text |Cite
|
Sign up to set email alerts
|

Imported parasitic wasp helps control red gum lerp psyllid

Abstract: The red gum lerp psyllid is an insect native to Australia, where it feeds upon eucalyptus species. Since 1998 this psyllid has spread throughout California, resulting in millions of dollars in damage and control costs. To help suppress the red gum lerp psyllid, a biological control program was initiated and a psyllid-specific parasitic wasp was imported from Australia in 1999 and released in 2000. In most coastal regions this biological control agent has provided substantial control, but in some interior regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 7 publications
0
30
0
3
Order By: Relevance
“…In 2001, the parasitoid, Psyllaphaegus bliteus, was released to control the psyllid (Paine and Millar 2002). This parasitoid is a specialist of G. brimblecombei in its native range in Australia where it is important in regulating psyllid populations (Dahlsten et al 2005). After release, successful establishment and population regulation by P. bliteus was found in some psyllid populations, but not in others (Dahlsten et al 2005).…”
Section: Anthropogenic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, the parasitoid, Psyllaphaegus bliteus, was released to control the psyllid (Paine and Millar 2002). This parasitoid is a specialist of G. brimblecombei in its native range in Australia where it is important in regulating psyllid populations (Dahlsten et al 2005). After release, successful establishment and population regulation by P. bliteus was found in some psyllid populations, but not in others (Dahlsten et al 2005).…”
Section: Anthropogenic Effectsmentioning
confidence: 99%
“…This parasitoid is a specialist of G. brimblecombei in its native range in Australia where it is important in regulating psyllid populations (Dahlsten et al 2005). After release, successful establishment and population regulation by P. bliteus was found in some psyllid populations, but not in others (Dahlsten et al 2005). A subsequent survey found that infection frequencies of a secondary endosymbont (Arsenophonus sp.…”
Section: Anthropogenic Effectsmentioning
confidence: 99%
“…Parasitism rates of blue gum lerp psyllid were 50-100% the year after parasitoid release Paine et al 2000). Moderate control of the red gum lerp psyllid has been achieved with the parasitoid P. bliteus Dahlsten et al 2005). The statewide average parasitism of red gum lerp psyllid was 22% .…”
Section: Discussionmentioning
confidence: 86%
“…An encyrtid parasitoid, Psyllaephagus bliteus, has established good biological control in many parts of California (34,35). Variability in the biological control could be a result of infection of the psyllid with an endosymbiotic bacterium that appears to confer some resistance to parasitism (68).…”
Section: North Americamentioning
confidence: 98%